Strategi Pemerintah dalam Pengembangan Ekowisata: (Studi di Kawasan Taman Nasional Bukit Tiga Puluh Kabupaten Indragiri Hulu Provinsi Riau) - Auradian Marta (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2014)
This study departs from the problems in the development of the Taman Nasional Bukit Tigapuluh (TNBT) in the region Indragiri Hulu Riau Province namely the destruction of ecosystems and inadequate infrastructure. This study seeks to examine the government's strategy in the development of the Taman Nasional Bukit Tigapuluh (TNBT). The research method in this study using kualititatif approach. This study showed that in the development of theTaman Nasional Bukit Tigapuluh (TNBT) includes planning, utilization and control is not running optimally. Synergy and cooperation between government agencies such as the Taman Nasional Bukit Tigapuluh (TNBT), the Regional Government of Riau Province, Local Government Indragiri upstream has not gone well so that the development of eco-tourism area is likely to be slow.